Temperature-dependent regulation of flowering by antagonistic FLM variants - Posé, David; Verhage, Leonie; Ott, Felix; Yant, Levi; Mathieu, Johannes; Angenent, Gerco C.; Immink, Richard G. H.; Schmid, Markus (Nature (London), 2013)
Temperature-dependent alternative splicing of FLOWERING LOCUS M ( FLM ) results in two protein products, FLM-β and FLM-δ, that regulate the onset of flowering in Arabidopsis ; at cooler temperatures FLM-β represses flowering, whereas at higher temperatures, the plant preferentially produces FLM-δ, which promotes flowering. Flowering when the temperature is right The transition to flowering is a critical event in the life cycle of a flowering plant and it needs to be timed precisely to ensure reproductive success. Here Markus Schmid and colleagues study the regulation of flowering in response to changes in ambient temperature. They show that temperature-dependent alternative splicing of FLOWERING LOCUS M ( FLM ) yields two protein products, FLM-β and FLM-δ, that regulate flowering in opposite ways. At cooler temperatures FLM-β represses flowering, whereas at higher temperatures the plant preferentially produces FLM-δ to promote flowering. Hence, temperature-dependent alternative pre-mRNA splicing controls the onset of flowering. The appropriate timing of flowering is crucial for plant reproductive success. It is therefore not surprising that intricate genetic networks have evolved to perceive and integrate both endogenous and environmental signals, such as carbohydrate and hormonal status, photoperiod and temperature 1 , 2 . In contrast to our detailed understanding of the vernalization pathway, little is known about how flowering time is controlled in response to changes in the ambient growth temperature. In Arabidopsis thaliana , the MADS-box transcription factor genes FLOWERING LOCUS M ( FLM ) and SHORT VEGETATIVE PHASE ( SVP ) have key roles in this process 3 , 4 . FLM is subject to temperature-dependent alternative splicing 3 . Here we report that the two main FLM protein splice variants, FLM-β and FLM-δ, compete for interaction with the floral repressor SVP. The SVP–FLM-β complex is predominately formed at low temperatures and prevents precocious flowering. By contrast, the competing SVP–FLM-δ complex is impaired in DNA binding and acts as a dominant-negative activator of flowering at higher temperatures. Our results show a new mechanism that controls the timing of the floral transition in response to changes in ambient temperature. A better understanding of how temperature controls the molecular mechanisms of flowering will be important to cope with current changes in global climate 5 , 6 .